Shifts in Chronic Disease Patterns Among Spanish Older Adults With Multimorbidity Between 2006 and 2017 - Jeroen J. A. Spijker; Elisenda Rentería (Frontiers Media S.A., 2023)
Objectives: To investigate changes in multimorbidity patterns among Spanish older adults.Methods: Data come from the Spanish National Health Survey (ENSE) for individuals aged 60-89 years (2006: n = 9,758; 2017: n = 8,535). Prevalence rates and relative risks of 20 chronic conditions are estimated for the multimorbidity (3+ chronic conditions) sample, along with observed-to-expected prevalence of three-way disease combinations. Principal component and cluster analyses identify multimorbidity patterns and track temporal changes.Results: Overall, multimorbidity remained stable [2006: 59.6% (95% CI: 58.7%-60.6%); 2017: 60.3% (CI: 59.3%-61.3%)], except at older ages. Women exhibited higher multimorbidity prevalence, but sex differences declined by five percentage points. Low-high education differences widened by three percentage points. In 2017 most individuals living with multimorbidity experienced hypertension (63.4%), osteoarthrosis (62.4%) and chronic back pain (55.9%). These chronic conditions also dominate the most common triadic combinations. Multimorbid men also saw increases in cholesterol and diabetes.Conclusion: Multimorbidity trends and the most common combination of diseases can help plan healthcare for an ageing population. Sex and socioeconomic differences pose additional public health challenges as women and deprived populations tend to have more health complexities.